Enterococcus faecium: evolution, adaptation, pathogenesis and emerging therapeutics - Wei, Yahan; Palacios Araya, Dennise; Palmer, Kelli L (Nature reviews. Microbiology, 2024)
The opportunistic pathogen Enterococcus faecium colonizes humans and a wide range of animals, endures numerous stresses, resists antibiotic treatment and stubbornly persists in clinical environments. The widespread application of antibiotics in hospitals and agriculture has contributed to the emergence of vancomycin-resistant E. faecium, which causes many hospital-acquired infections. In this Review, we explore recent discoveries about the evolutionary history, the environmental adaptation and the colonization and dissemination mechanisms of E. faecium and vancomycin-resistant E. faecium. These studies provide critical insights necessary for developing novel preventive and therapeutic approaches against vancomycin-resistant E. faecium and also reveal the intricate interrelationships between the environment, the microorganism and the host, providing knowledge that is broadly relevant to how antibiotic-resistant pathogens emerge and endure.